Evaluación de los riesgos de afectación por el establecimiento de granjas atuneras en relación con la distribución espacial de cetáceos en el Golfo Dulce, Costa Rica - Oviedo Correa, Lenin E.; Pacheco, Juan Diego; Herra Miranda, David (2009)
This contribution deals with the spatial distribution of marine top predators, particularly odontocete and migratory misticete cetaceans. The study describes the potential risk of disturbances due to the establishment of mariculture operations and corresponding infrastructure: tuna feed lots. Through a mixed theoretical and empirical approach, this research corroborates how the maximum depth, a limiting factor in the definition of cetacean trophic niches off the study area, overlaps with the values for depths from an area proposed as the focal location of a tuna feed lot facility. The latter implies two particular scenarios: the translocation of the local predator population from a potential foraging habitat-niche, and the progressive negative interaction between predators and the accompanying fish fauna around of the cages, with a high probability of incidental capture of those predators by entanglement. Additionally, the occurrence of humpback whales during the rainy season associated with a migratory route from feeding grounds off Chile-Antarctica, that would pass through the area projected to harbor the mariculture operation. The results illustrate the need of considering a precautionary approach and relocate mariculture projects to areas of lesser value in terms of marine biodiversity. Este estudio trata sobre la distribución espacial de depredadores marinos topes, particularmente cetáceos odontocetos y misticetos migratorios. Se describe el riesgo potencial de afectación por el establecimiento de instalaciones asociadas con operaciones locales de maricultura: jaulas de engorde para atún. Por medio de un enfoque teórico y empírico se establece cuantitativamente como la profundidad máxima, un factor limitante en la distribución y definición del nicho ecológico de cetáceos, se solaparía en valores con el área propuesta para el establecimiento de las jaulas, lo que induciría dos escenarios probables de afectación: el desplazamiento de las poblaciones de depredadores de un hábitat-nicho de alimentación ...